Development of Tourist Destinations Based on the Use of the Intangible Cultural Heritage of Ukraine as a Tool for Creating a Unique Ethnocultural Brand - Volodymyr Antonenko (Socio-Cultural Management Journal)
Abstract: Introduction. The article is a comprehensive study that provides a thorough analysis of the intangible cultural heritage (hereinafter referred to as the ICH) of Ukraine as a basis for the formation of an ethnocultural brand of a tourist destination. The essential characteristics of forming an ethnocultural tourist destination brand based on marketing tools for popularising ICH are revealed. The key role of ICH in preserving national identity and developing tourism in the context of globalisation is highlighted. The purpose of the article is to provide a theoretical and methodological justification for the study of the intangible cultural heritage of Ukraine as an ethnocultural brand of a tourist destination. The study employed general scientific methods of cognition: analysis and synthesis, comparison, induction and deduction, generalisation, and historical and logical approaches. Results. The research findings indicate that tourism activities act as an effective mechanism for actively using intangible cultural heritage in modern conditions, creating platforms for reproducing traditions, crafts and rituals. This process contributes to the preservation of cultural diversity, the development of tourism infrastructure and the attraction of new audiences. The use of intangible cultural heritage as a basis for the formation of tourism products allows you to create authentic and competitive brands that combine traditional values with modern marketing approaches. The results obtained can be used to develop strategies for the popularisation of intangible cultural heritage, the creation of new tourist routes, the improvement of cultural policy in the context of sustainable development, and the creation of an ethno-cultural brand of Ukraine. Conclusions. The study concludes that ICH promotes high-quality tourism development, and tourism supports the bilateral expansion of living heritage opportunities. Tourism activity provides scenarios for the application of ICH. It indicates the direction of its activation and use, as an essential resource for tourism development, since it not only preserves the unique cultural identity, but also contributes to the economic growth of regions. Integrating ICH elements in forming tourism products allows for creating an authentic and competitive tourism brand for Ukraine.